Identifying the Electrostatic and Entropy‐Related Mechanisms for Charge‐Transfer Exciton Dissociation at Doped Organic Heterojunctions. (17th April 2021) - Xue, Wenyue; Tang, Yabing; Zhou, Xiaobo; Tang, Zheng; Zhao, Hanzhang; Li, Tao; Zhang, Lu; Liu, Shengzhong (Frank); Zhao, Chao; Ma, Wei; Yan, Han
Abstract: The electron donor/acceptor (D/A) heterojunction is the core for photocharge generation and recombination in organic photovoltaics (OPVs). Developing practical methods for the D/A heterojunction modification remains challenging and is rarely discussed in OPV research. Herein, the roles of molecular doping at the D/A heterojunction in the charge‐transfer exciton dissociation and detailed energy loss are investigated, and new insights are gained into the functions of doping on the OPV performance. Heterojunction doping simultaneously enhances all three OPV parameters, especially the short‐circuit current ( J sc ). It is shown that the J sc improvement is due to the combined effects of strengthened electric field and reduced activation energy, which is regulated via an entropy‐related mechanism. The performance enhancement is further demonstrated in homojunction devices showing the great potential of interfacial doping to overcome the intrinsic limitation between high J sc and open‐circuit voltage ( V oc ) in OPVs. Abstract : Direct electrical property regulation of organic semiconductors by heterojunction molecular doping is applied to improve photovoltaic performance in planar heterojunction model devices. The upward charge‐transfer state movement and reduced non‐radiative recombination increase V oc . The significant 20% J sc increment is ascribed to the doping modified electrostatic field and the entropy‐related activation process at organic heterojunctions.